2017
DOI: 10.1139/cjce-2017-0132
|View full text |Cite
|
Sign up to set email alerts
|

Development of an artificial neural network model to predict subgrade resilient modulus from continuous deflection testing

Abstract: Abstract:The subgrade resilient modulus is an important parameter in pavement analysis and design. However, available non-destructive testing devices such as the falling weight deflectometer (FWD) have limitations that prevent their widespread use at the network level. This study describes the development of a model that utilizes the rolling wheel deflectometer (RWD) measurements to predict the subgrade resilient modulus at the network level for flexible pavements. Measurements of RWD and FWD obtained from a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The first 70% of the data was utilized for training the model, while the remaining 30% of the data was divided into model testing and validation data sets. As shown in Figure 5, as an effort to avoid overfitting and maintain network generalization, the D r a f t training was stopped when the validation data set error had stopped decreasing (Elbagalati et al 2017).…”
Section: Model Training Methodology and Evaluationmentioning
confidence: 99%
“…The first 70% of the data was utilized for training the model, while the remaining 30% of the data was divided into model testing and validation data sets. As shown in Figure 5, as an effort to avoid overfitting and maintain network generalization, the D r a f t training was stopped when the validation data set error had stopped decreasing (Elbagalati et al 2017).…”
Section: Model Training Methodology and Evaluationmentioning
confidence: 99%
“…In order to examine the efficacious stabilization of extremely weak subgrade soils at high water contents, the resilient modulus of stabilized subgrade was determined; therefore, ANN and GEP models were formulated by considering 125 samples data and it was concluded that accurate result for M r was achieved by using GEP (R 2 of 0.95) [17]. In yet another study regarding prediction of M r , the computation of a rolling-wheel deflectometer and a falling weight deflectometer was yielded from a testing program for training an ANN-based model, which was independently validated using data from a testing program, such that it depicted an acceptable accuracy in both the development and validation phases (R 2 of 0.73 and 0.72, respectively) [66]. Moreover, Jalal et al [57] suggested that the genetic programming approaches (i.e., GEP and MEP) techniques accurately forecast the compaction characteristics (maximum dry density and optimum moisture content) of swelling clays, such that the GEP model showed a relatively better performance.…”
Section: Introductionmentioning
confidence: 99%
“…For flexible pavements, the random cracking index (RNDM) encompasses all random cracks, which include thermal, reflective, longitudinal, block, and cement-treated reflective cracks. The equations used to calculate the alligator cracking index (ALCR), the random cracking index (RNDM), the roughness index (ROUGH), and the rutting index (RUTT) are as follows ( 6 ):…”
Section: Introductionmentioning
confidence: 99%
“…Cost-efficiency of RWD testing was evaluated in light of the added economic benefits ( 5 ). Methodologies for backcalculation of subgrade moduli based on RWD measurements and layer moduli based on TSD measurements were developed ( 6 , 7 ). In addition, a framework was developed to incorporate RWD measurements in the Louisiana pavement management system (PMS) at the network level and in asphalt concrete (AC) overlay design at the project level ( 8 , 9 ).…”
mentioning
confidence: 99%